The cash flow tax as a local business tax - Dieter Cansier (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1990)
In the discussion on reforming the local business tax, little attention has been payed until now to the cash flow tax, although this tax opens up interesting perspectives and has been intensively discussed in tax theory.) For this reason we want to examine the suitablilty of the cash-flow tax for use as a local business tax, and in particular how this tax fares in comparison with the existing local business tax as well as with the local value added tax which has been proposed by the Finanzwissenschaftlicher Beirat beim Bundesfinanzministerium). The criteria for this comparison arise from the special requirements of a local tax: It should be cyclically neutral, simple to impose, show only a slight geographical dispersion in its revenues and enable a just distribution of the tax bürden according to the benefit principle.
Keywords: 330